2024
DOI: 10.3390/microorganisms12010161
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Diagnosis and Treatment Approaches in Fungal Keratitis: A Narrative Review

Laura Andreea Ghenciu,
Alexandra Corina Faur,
Sorin Lucian Bolintineanu
et al.

Abstract: Fungal keratitis represents a potentially sight-threatening infection associated with poor prognosis, as well as financial burden. Novel diagnostic methods include polymerase-chain-reaction (PCR)-based approaches, metagenomic deep sequences, in vivo confocal microscopy, and antifungal susceptibility testing. The ideal therapeutic approaches and outcomes have been widely discussed in recent times, with early therapy being of the utmost importance for the preservation of visual acuity, minimizing corneal damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 98 publications
1
5
0
Order By: Relevance
“…The male population represented 59.38%, and 56.7% the patients were from urban areas. In comparison with other studies, the gender di bution and regional origin within this cohort appear consistent with general demograp trends [1,3,[28][29][30]. However, the median age at diagnosis and examination, along with wide interquartile range, suggest variability in the timing of anomaly detection and c cal assessment, which may differ from findings in other populations; each country different health care systems, the number of antenatal scans as per protocol varies and addressability of an ultrasound depends on the socio-economic status of the coun [1,28].…”
Section: Discussionsupporting
confidence: 90%
“…The male population represented 59.38%, and 56.7% the patients were from urban areas. In comparison with other studies, the gender di bution and regional origin within this cohort appear consistent with general demograp trends [1,3,[28][29][30]. However, the median age at diagnosis and examination, along with wide interquartile range, suggest variability in the timing of anomaly detection and c cal assessment, which may differ from findings in other populations; each country different health care systems, the number of antenatal scans as per protocol varies and addressability of an ultrasound depends on the socio-economic status of the coun [1,28].…”
Section: Discussionsupporting
confidence: 90%
“…This study investigated the effects of SARS-CoV-2 infection on newborns and young children, using a real-time multiplex PCR (Polymerase Chain Reaction) test for diagnosis [26]. This study meticulously watched and recorded numerous indicators and symptoms with the purpose of comprehending the wide range of consequences this virus has on these patients.…”
Section: Methodsmentioning
confidence: 99%
“…Preclinical studies utilizing gene therapy to inhibit aldose reductase expression or activity have shown promising results in animal models of diabetic retinopathy. These studies have demonstrated improvements in retinal function, preservation of retinal structure, and attenuation of vascular abnormalities following gene-based aldose reductase inhibition [59]. While these preclinical findings are encouraging, translating gene therapy approaches targeting aldose reductase inhibition into clinical practice for DR requires further investigation.…”
Section: Gene Therapymentioning
confidence: 99%
“…There have been a few studies using Western blot for the determination of AR in various tissues before and after treatment with an ARI [53]. Quantitative real-time PCR (qRT-PCR) is a accurate and efficient molecular investigation [59], which can be utilized to measure aldose reductase mRNA…”
Section: Measurement Of Aldose Reductasementioning
confidence: 99%
See 1 more Smart Citation